2020
DOI: 10.3390/su12219004
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Risk Factors and Protective Role of Resilience and Coping Strategies for Emergency Stress and Secondary Trauma in Medical Staff and Emergency Workers—An Online-Based Inquiry

Abstract: The COVID-19 crisis has placed a heavy burden on medical staff and emergency workers, who may be at risk of developing psychological distress and secondary trauma. Coping and resilience to stress during a pandemic are protective factors that can mitigate the potential adverse psychological effects. Here, we investigated the direct and mediated effects of coping strategies and hardiness on secondary trauma among Italian medical staff (physicians and nurses, n = 140) and emergency workers (firefighters, civil pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
2
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(108 citation statements)
references
References 90 publications
8
86
2
12
Order By: Relevance
“…Nine studies described the interaction between coping skills and mental health in HCWs during the COVID-19 pandemic (Baboe et al ., 2020; Chew et al ., 2020; Di Monte et al ., 2020; Hou et al ., 2020; Maiorano et al ., 2020; Mi et al ., 2020; Nie et al ., 2020; Vagni et al ., 2020; Zhu et al ., 2020;). The use of positive coping mechanisms such as seeking social support, positive thinking, and problem solving were associated with lower levels of traumatic stress, stigma (Chew et al ., 2020), psychological distress (Baboe et al ., 2020), stress symptoms (Nie et al ., 2020), anxiety, and depression (Zhu et al ., 2020; Mi et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies described the interaction between coping skills and mental health in HCWs during the COVID-19 pandemic (Baboe et al ., 2020; Chew et al ., 2020; Di Monte et al ., 2020; Hou et al ., 2020; Maiorano et al ., 2020; Mi et al ., 2020; Nie et al ., 2020; Vagni et al ., 2020; Zhu et al ., 2020;). The use of positive coping mechanisms such as seeking social support, positive thinking, and problem solving were associated with lower levels of traumatic stress, stigma (Chew et al ., 2020), psychological distress (Baboe et al ., 2020), stress symptoms (Nie et al ., 2020), anxiety, and depression (Zhu et al ., 2020; Mi et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In one study, the use of emotion-centred and avoidant coping styles were associated with increased levels of emotional exhaustion, while problem-centred coping styles were strongly associated with decreased scores on the depersonalization subscale and increased scores on the personal accomplishment subscale of the MBI (Di Monte et al ., 2020). Interestingly, unlike previous studies, a two separate studies in Italy found that the use of a negative coping style – specifically, the blocking of unpleasant emotions and thoughts – was found to effectively reduce psychological distress (Vagni et al ., 2020) and PTSD (Maiorano et al ., 2020). Vagni et al .…”
Section: Methodsmentioning
confidence: 99%
“…Reports from all over the world have already ascertained that HCWs have significant levels of self-reported anxiety, depression, insomnia and even symptoms of post-traumatic stress disorder ( Buselli et al, 2020a , 2020b ; Digby et al, 2020 ; Firew et al, 2020 ; Krishnamoorthy et al, 2020 ; Maiorano et al, 2020 ; Pappa et al, 2020 ; Trumello et al, 2020 ; Vagni et al, 2020 ) and a recent canadian meta-analysis further evidenced that the prevalence of insomnia seems to be more than two times higher among HCWs than in the general population ( Cenat et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most difficult moments occurred especially during the first weeks of pandemic when HCPs had to deal with insufficient personal protective equipment (i.e., gowns, masks, and face shields) [ 3 ] which exposed the personnel to higher risk of contracting coronavirus than the general public [ 4 ] making it particularly vulnerable [ 4 , 5 , 6 , 7 ]. These objective difficulties were coupled with psychological difficulties linked to the fear of contracting the virus, infecting one’s family members, and, above all, to one’s sense of helplessness in the face of patient losses [ 8 ].…”
Section: Introductionmentioning
confidence: 99%